Estimating the cardiovascular mortality burden attributable to the European Common Agricultural Policy on dietary saturated fats - Ffion Lloyd-Williams; Martin O'Flaherty; Modi Mwatsama; Christopher Birt; Robin Ireland; Simon Capewell (The World Health Organization, 2008)
OBJECTIVE: To estimate the burden of cardiovascular disease within 15 European Union countries (before the 2004 enlargement) as a result of excess dietary saturated fats attributable to the Common Agricultural Policy (CAP). METHODS: A spreadsheet model was developed to synthesize data on population, diet, cholesterol levels and mortality rates. A conservative estimate of a reduction in saturated fat consumption of just 2.2 g was chosen, representing 1% of daily energy intake. The fall in serum cholesterol concentration was then calculated, assuming that this 1% reduction in saturated fat consumption was replaced with 0.5% monounsaturated and 0.5% polyunsaturated fats. The resulting reduction in cardiovascular and stroke deaths was then estimated, and a sensitivity analysis conducted. FINDINGS: Reducing saturated fat consumption by 1% and increasing monounsaturated and polyunsaturated fat by 0.5% each would lower blood cholesterol levels by approximately 0.06 mmol/l, resulting in approximately 9800 fewer coronary heart disease deaths and 3000 fewer stroke deaths each year. CONCLUSION: The cardiovascular disease burden attributable to CAP appears substantial. Furthermore, these calculations were conservative estimates, and the true mortality burden may be higher. The analysis contributes to the current wider debate concerning the relationship between CAP, health and chronic disease across Europe, together with recent international developments and commitments to reduce chronic diseases. The reported mortality estimates should be considered in relation to the current CAP and any future reforms.